PENERAPAN STRATEGI DRTA (DIRECTED READING THINKING ACTIVITY) DALAM PEMBELAJARAN MEMBACA PEMAHAMAN SISWA TUNARUNGU KELAS VIII DI SLB - RODIYAH, SITI (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   Hearing impairment children had difficulty in one of the language skill aspects i.e. reading comprehension which was resulted by the hearing impairment so it had impact to the language development. Reading comprehension ability had very important position because reading comprehension was the media to enlarge knowledge and add perception in enhancing intelligence. Hearing disorder experienced by the hearing impairment children could delay learning progress in the meaning of understanding the reading content. Based on the explanation above, this research had purpose to know the influence of DRTA strategy application toward reading comprehension ability to hearing impairment students of class VIII in SMPLB-B Karya Mulia Surabaya. The kind of research used was pre experiment using “the one group pre-test post-test design”. The subject in this research was hearing impairment students of class VIII in SMPLB-B Karya Mulia Surabaya numbering 6 students who had difficulty in reading comprehension. The data collection technique was collected by using test and observation. The intervention implication was done in 6 times meeting with the time allocation 3 x 40 minutes each meeting. The data analysis technique used statistic non parametric of wilcoxon match pair test. The data analysis result of Z value obtained from counting was 2,20 greater than Z table to critic value = 5% i.e. 1,96 so null hypothesis (Ho) was refused and work hypothesis (Ha) was accepted. The research conclusion was that there was significant influence of DRTA (Directed Reading Thinking Activity) strategy application toward reading comprehension ability to hearing impairment students of class VIII in SMPLB-B Karya Mulia Surabaya.   .   Keywords: Learning Strategy, reading comprehension.